The use of ON-OFF and ANN Controllers for Automated Irrigation System Model Based on Penman-Monteith Evapotranspiration - Susilo Adi Widyanto; Achmad Widodo; Achmad Hidayatno; Suwoko Suwoko (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
The climate change tends to be extreme condition that directly affects on decreasing agriculture production.  Therefore, application of automated system in agriculture activities is the potential issue which must be considered. This paper presents ON-OFF and ANN controllers which are applied to the automated irrigation system. Controlling irrigation system used a calculated Penman-Monteith evapotranspiration and a reference of soil moisture as the compared input. Input parameters of the evapotranspiration included temperature, heat radiation, atmosphere pressure and wind speed. The use of feed forward ANN included 1 input layer with 15 neurons and 2 hidden layers with 10 and 5 neurons and 1 output layer and 1 input layer, 2 hidden layers with 96 and 1 neurons and 1 output layer, errors are 14.3% and 3.9%, respectively. Error of the ON-OFF controller with sampling time of 0.05 second is equal to the error of ANN controller. The performance of such controllers were evaluated and compared based on error of both controllers.  The simulation result of ON-OFF controller was used as the reference of controller development based on ATmega 8 microcontroller. The simulation results show that the error of the ON-OFF controller can be easily adjusted by setting the sampling time of the dead zone discretization.